Experimental supply demand analysis of yeast fermentative free energy metabolism : an in vivo and in situ investigation - Smith, Justin Alan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2010.